A Dose–response relationship between severity of disc degeneration and intervertebral disc height in the lumbosacral spine. Issue 1 (December 2015) - Teichtahl, Andrew; Urquhart, Donna; Wang, Yuanyuan; Wluka, Anita; Heritier, Stephane; Cicuttini, Flavia
Abstract Introduction Varied definitions of disc pathology exist in the literature. Magnetic Resonance Imaging (MRI) classification systems incorporate several qualitative features including disc appearance, the distinction between the nucleus and the annulus, signal intensity and intervertebral disc height. The lack of a continuous measure has made it difficult to sensitively examine degenerative disc disease. This study sought to examine the relationship between disc degeneration and intervertebral disc height. Methods 72 community-based individuals not selected for low back pain had MRI from which the presence of lumbosacral disc degeneration was identified using the Pfirrmann grading system, and intervertebral disc height was measured. Results At each lumbosacral level, with higher grade of disc degeneration, intervertebral disc height was reduced (all p ≤ 0.003). Results remained unchanged when grade 5 disc degeneration, which necessitated a collapsed disc space, was excluded from analyses (all p ≤ 0.03). To quantify these associations, at each lumbosacral level, for every grade increase in disc degeneration, there was a reduction in intervertebral disc height, after adjusting for age, gender, Body mass index and smoking history (β range from −0.98 mm to −1.60 mm, 95 % CI range from −2.37 to −0.31, all p ≤ 0.005). Conclusion This study has demonstrated a negative dose–response relationship between increasing severity of disc degeneration with a reduction in intervertebral disc height. Although the assessment of disc degeneration incorporates a number of qualitative measures, these data substantiate the utility of intervertebral disc height as a quantitative and continuous outcome measure in epidemiological studies, and potentially clinical practice.